2018
DOI: 10.1094/mpmi-07-17-0173-fi
|View full text |Cite
|
Sign up to set email alerts
|

Suppression or Activation of Immune Responses by Predicted Secreted Proteins of the Soybean Rust Pathogen Phakopsora pachyrhizi

Abstract: Rust fungi, such as the soybean rust pathogen Phakopsora pachyrhizi, are major threats to crop production. They form specialized haustoria that are hyphal structures intimately associated with host-plant cell membranes. These haustoria have roles in acquiring nutrients and secreting effector proteins that manipulate host immune systems. Functional characterization of effector proteins of rust fungi is important for understanding mechanisms that underlie their virulence and pathogenicity. Hundreds of candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 71 publications
3
38
0
Order By: Relevance
“…One of the most advanced effectoromic screens performed in rust fungi was recently reported for P. pachyrhizi (Qi et al ., ). The selection of 82 candidate effectors (PpECs) was based on haustoria RNAseq (Link T. et al ., ; Link T.I.…”
Section: Functional Characterization Of Rust Effectorsmentioning
confidence: 97%
See 3 more Smart Citations
“…One of the most advanced effectoromic screens performed in rust fungi was recently reported for P. pachyrhizi (Qi et al ., ). The selection of 82 candidate effectors (PpECs) was based on haustoria RNAseq (Link T. et al ., ; Link T.I.…”
Section: Functional Characterization Of Rust Effectorsmentioning
confidence: 97%
“…benthamiana ; assay induction of an immune response in pepper and tomato; and assay cell death suppression in N. benthamiana , Arabidopsis and yeast. Among the 82 PpECs, 17 suppress plant immunity and 30 PpECs target different cell compartments, such as nucleus, nucleolus and cytoplasm (Qi et al ., ). The secretion of one candidate, PpEC23, was confirmed in yeast and it was further shown to suppress the immune response in soybean.…”
Section: Functional Characterization Of Rust Effectorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Discrimination of SPs in each Gymnosporangium spp. helps to narrow down the list of specific candidates and will support future effector studies to better understand the biology of infection as demonstrated for other rust species [50][51][52]. The transcriptome of G. japonicum and its comparison to other…”
mentioning
confidence: 97%